Investigating Performance Installation of Hospital Room Surgery of Six Hospitals in Special Region of Yogyakarta by Using Data Envelopment Analysis Model Constant Return to Scale - Bhimo Rizky Samudro; Yogi Pasca Pratama (Universitas Muhammadiyah Ponorogo, 2018)
This study aims to investigate the efficiency level of hospital surgery hospital installation in Special Region of Yogyakarta Province. Research conceptual constructs are based on input and output performance in institutional performance processes. This research approach uses positivist pattern and is derived by quantitative method. This is to explain the efficiency pattern of the installation of hospital and private hospital surgery rooms. The quantitative method chosen is the concept of Data Envelopment Analysis (DEA). The results showed that 1) the installation of a private hospital surgery room tends to be more efficient than government property; 2) the installation of a special hospital surgical hospital is not absolutely more efficient than a public hospital. As a recommendation, this research provides scenario for setting input usage for efficient performance.